Plio-pleistocene palaeoenvironment of the south western continental shelf of South Africa: a foraminiferal perspective - Walsh, Jared Tanner (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.